IgH enhancer deregulated expression of L-myc: abnormal T lymphocyte development and T cell lymphomagenesis. - Möröy, T (1990)
Transgenic constructs containing the murine L-myc gene under the control of the immunoglobulin transcriptional enhancer element (Emu) are expressed at unexpectedly high levels in thymocytes and proliferating T cells compared with cells from bone marrow and proliferating B cells. In contrast, double transgenic animals bearing constructs containing the L- and N-myc genes similarly linked to the Emu element maintain preferential L-myc expression in T cells but express the N-myc transgene preferentially in B cells. These results indicate that the L-myc gene contains elements that act in concert with the Emu element to allow preferential expression in T lineage cells. In correspondence to the expression pattern, Emu-L-myc transgenic mice show expanded thymic cortices and irregularly formed splenic follicles with expanded T cell areas. Moreover, the percentage of thymocytes positive for the surface marker 1C11, which defines thymic progenitor cells, activated T cells and preleukemic T cells, is dramatically raised in transgenic mice compared with normal littermates. Emu-L-myc transgenic animals are predisposed to clonal lymphoid tumors, most of which are T cell lymphomas. The relative incidence, latency period, and degree of malignancy of Emu-L-myc tumors compared with Emu-N- or c-myc tumors is consistent with a lower oncogenic potential of the L-myc gene. However, the Emu-L-myc tumors do not express detectable levels of endogenous myc family genes indicating that the L-myc protein can substitute for c- or N-myc in the generation and growth of lymphoid neoplasms.